Treatment of Severe Emotionally Unstable Personality Disorder with Comorbid Ehlers-Danlos Syndrome and Functional Neurological Disorder in an Inpatient Setting: A Case for Specialist Units without Restrictive Interventions. (25th February 2021) - Henry, Jessica; Collins, Eddie; Griffin, Amanda; Zimbron, Jorge
Abstract : We present the case of a young woman with an Emotionally Unstable Personality Disorder (EUPD) diagnosis suffering from high-risk self-injurious behaviour. She was also diagnosed with Ehlers-Danlos Syndrome and Functional Neurological Disorder, manifesting as nonepileptic seizures and immobility. Our patient, "A, " endured traumatic childhood abuse and became highly dependent on services in her late teens. Recurrent suicide attempts resulted in twenty to thirty acute psychiatric admissions, Intensive Care Unit stays, and multiple failed trials of psychological therapy. Nonepileptic seizures and wheelchair dependency made her "too complex" for many specialist services. She was eventually admitted to Springbank ward in Fulbourn Hospital, Cambridge. The EUPD specialist unit prides itself on evidence-based treatments, shared values, and a least restrictive approach. At discharge, our patient was self-harm free and able to walk unaided and no longer met EUPD diagnostic criteria. We include "A's" personal views on her illness and how Springbank ward facilitated her recovery, together with results from structured clinical outcome measures.